Threats to Our Ocean Heritage: Potentially Polluting Wrecks
XII, 159 p. 33 illus. in color.
Keywords: This open access volume focuses on the environmental hazards and cultural significance of Potentially Polluting Wrecks (PPWs), and how mitigation efforts have assisted in documenting and preserving the history of these sites. It is an important resource on the subject of Potentially Polluting Wrecks that synthesizes previously published information that was not academically or scientifically produced. This includes numerous international studies of shipwreck databases and threats posed by world war wrecks containing oil and other hazardous materials that could spill. This book evaluates these materials and presents new analyses and investigations with modern technology that assist in locating, documenting, and remediating polluting wreck sites. Consequently, this volume calls for increased ocean exploration missions to locate sunken merchant vessels that may pose pollution hazards and site assessments to determine any potential risks. This book is of interest to government officials, educators, archaeologists and practitioners working in the field of underwater archaeology.